Strategi Komunikasi Pemerintah Desa Sebagai Langkah Taktis Penanganan Dan Pencegahan Covid-19 - Gading Gamaputra; Agus Prasetyawan; Prasetyo Isbandodo; Yuni Lestari; Alvionita Fitria Putri; M Syarif Hidayatullah; Noviyanti Noviyanti (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2021)
Abstract The Tuban Regency Government issued a Regent Decree No. 440/1592/414.103/2020 concerning Increased Awareness of Covid-19 in Tuban Regency. All villages in Tuban Regency are required to carry out a program of handling and preventing Covid-19 activities. Covid-19 handling and prevention The Kesamben Village Government is experiencing problems, including the public's distrust of the dangers of Covid-19 due to lack of accurate data, information and low public trust regarding the handling of COVID-19 in Indonesia. To overcome this problem, the Kesamben Village Government carried out a communication strategy to the community so that the implementation and handling of Covid-19 activities were carried out properly and became a pilot village for handling COVID-19 in Tuban Regency. The research used in this research is descriptive qualitative by focusing on the first, the tactical steps of the Kesamben Village Government in the Prevention and Handling of Covid-19. Second, the communication strategy for the prevention and handling of Covid- 19 Keywords: Corona Virus Disease 2019 (covid-19), Village Government Communication Strategy.